P124 Study of DNA repair gene polymorphisms in ovarian cancer. (1st November 2019) - Gomes Ferreira, M; Ovejero-Sanchez, M; Sanchez Tapia, E; Martin-Gómez, T; Vidal, R; Sancho de Salas, M; Doyague Sanchez, MJ; Gonzalez-Sarmiento, R
Abstract : Introduction/Background: Ovarian cancer (OC) is proven to be influenced by alterations in some DNA repair genes (e.g. BRCA1/2). In our work, we analyzed in DNA repair genes polymorphisms (SNPs) by TaqMan genotyping in OC peripheral blood samples. Methodology: An association study of SNPs rs1799782, rs25487, rs1130409, rs13181, rs11615, rs1799794, rs861539, rs1042522, rs1799977 and rs1800734 of genes XRCC1, APEX1, ERCC2, ERCC1, XRCC3, MLH1 and TP53 was performed in the germinal DNA of 185 patients and 129 healthy controls. Results: The GA genotype of XRCC1 polymorphism rs1799782, the CC genotype of TP53 polymorphism rs1042522 and the GG genotype of MLH1 polymorphism rs1800734 were associated with increased susceptibility to OC. The T allele of APEX1 polymorphism rs1130409 was associated with a later onset of the disease and hereditary OC. In relation to XRCC3 gene (rs1799794), the TT genotype was associated with increased OC susceptibility in aging patients and patients with familial OC. In relation to MLH1 gene (rs1800734), the GG genotype was associated with greater OC susceptibility in old patients and in patients with hereditary OC. The SNP rs1799977 of MLH1 gene was associated with an increased risk of recurrence. Conclusion: Our study suggests that DNA repair genes different from BRCA1/2 like XRCC1, TP53, MLH1, XRCC3 and APEX1 could modify the risk of developing OC. This project was funded by FIS-FEDER PI16/01920. Disclosure: Nothing to disclose.